Shades of grey [compact disc, unabridged] : a novel - Fforde, Jasper (Penguin Audio, 2009)
Jasper Fforde unfolds the tale of Eddie Russett, a boy living in a world without color. As he works for the Color Control Agency, the very entity that oppresses society's ability to see colors, Eddie falls in love with Jane, a girl from the unlit side of the village. However, when the two start to discuss rebelling against their oppressors, they undertake an adventure of a lifetime.